PENGARUH EARNING PER SHARE, RETURN SAHAM, KUALITAS AUDIT, DAN HASIL LABA TERHADAP RETURN SAHAM SATU TAHUN KE DEPAN (Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2010-2011) - Muhammad Husni Nurrohman; Zulaikha Zulaikha (Diponegoro Journal of Accounting, 2013)
The purpose of this research was to examine the effect of analysis factor-factor has influence on stock returns one year ahead. The independent variable in this study was the Earning per Share (EPS), current period of stock returns, audit quality, and the company's profit who were reported profit or loss. Stock returns one year ahead was the dependent variable which measured using the current period stock price, the previous year stock price, and the current dividend period. The sample used in this study was a manufacturing company listed on Indonesia Stock Exchange (IDX) during 2010-2011. Sampling’s technique used was purposive sampling, which results in 55 samples of manufacturing firms. Analysis technique used was multiple regression with SPSS 20.The result show that the earnings per share and operational profit doesn’t significant influence to the stock returns one year ahea,; the stock returns and audit quality had positive effect significantly the stock returns one year ahead.